Fin-tech Regulations Development, Challenges, and Solutions : A Review - Gupta, Chander Mohan; Kaur, Gagandeep; Yuliantiningsih, Aryuni (Jurnal Dinamika Hukum, 2024)
Fintech is a term which is the most common and used in the financial sector these days around the globe. Its growth has made it clear that it is there to stay, and it is going to cause a major disruption on the globe level, when talked about in relation to financial markets. It is an old saying, “With great powers come great responsibilities” and the same is true in relation to fintech. With the kind of growth, it is doing it needs to be monitored and regulated on a major level. When we talk about the fast-moving areas where fintech has made an impact are e-invoice, e-payments, deposits, and financial transactions on personal, corporate and government level. When we calculate the scale at which fintech is growing we need to understand that it is just a matter of time that everything will be assessable with a click of a button and if in the wrong hands we can imagine the impact done. When we see the dark side of fintech where the companies have an assesses to the data and every personal information of customers, they can use/misuse the same at their liberty. If we study the cases from around the globe it is a simple practice of which works of a simple rule, “If it works here, it will work everywhere.” This paper also delves into tracing the cyber threats faced by the financial sector due to its reliance on technology and sensitive data.  The authors have analysed a number of laws, rules, and guidelines to regulate fintech in India that are designed to foster innovation, protect the interests of consumers, and preserve the country's financial stability.   Thus, in the said paper the authors have tried to study the journey of Fintech in relation to its regulatory legal journey, in relation to India.